1998
DOI: 10.1097/00003246-199801000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Aerosolized antibiotics in mechanically ventilated patients

Abstract: Nebulizer delivery of aerosolized aminoglycosides is efficient and predictable. In our clinical model, aerosolized antibiotics can make a significant impact on respiratory secretions. Their efficacy in treatment of critically ill patients remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(87 citation statements)
references
References 36 publications
2
82
0
3
Order By: Relevance
“…Aerosol delivery provides a means to achieve local effects in the lung with minimal systemic drug exposure [33]. Estimates of the current authors nebulisation system suggests that it deposits 12-20% of output to the 17th-23rd generation of the bronchials, the transitory zones leading to terminal alveolated lung [33].…”
Section: Discussionmentioning
confidence: 99%
“…Aerosol delivery provides a means to achieve local effects in the lung with minimal systemic drug exposure [33]. Estimates of the current authors nebulisation system suggests that it deposits 12-20% of output to the 17th-23rd generation of the bronchials, the transitory zones leading to terminal alveolated lung [33].…”
Section: Discussionmentioning
confidence: 99%
“…LPS (endotoxin, O antigen) is a membrane structural component of all gram negative bacteria [31]. The structur al alterations of a bacterial membrane results in endotoxemia since one bacteria contain up to 3 500 000 LPS molecules.…”
Section: Resultsmentioning
confidence: 99%
“…When used continually, rather than intermittently, oropharyngeal antibiotics were associated with an increased incidence of pneumonia with resistant bacteria and this regimen was abandoned (Feeley et al 1975). Palmer et al (1998) demonstrated that nebulised antibiotics can be effectively delivered to patients receiving mechanical ventilation, with measurable changes in clinical and airway inflammatory indicators (decreased levels of inflammatory cells and mediators), significant reduction in sputum volume, and eradication of P. aeruginosa and other Gram-negative pathogens in most cases. The study involved only six patients who received nine courses of either nebulised gentamicin or amikacin for 14±21 days.…”
Section: Aerosolised Antibioticsmentioning
confidence: 99%